Revolutionizing Rural Credit Banks: A Narrative Review of Sustainable Financial Futures through ESG Integration and Digital Innovation - Bustani, Bustani (Universitas Dehasen Bengkulu, 2025)
This study presents a narrative review of the transformation of Rural Credit Banks (BPR) through the integration of Environmental, Social, and Governance (ESG) principles and digital innovation, aiming to explore the future of sustainable finance. BPR plays a strategic role in expanding financial inclusion and strengthening the local economy, yet it faces complex challenges amid global economic dynamics. This research identifies three main pillars of BPR transformation: (1) the integration of ESG principles into governance, (2) the adoption of digital technology for efficiency, and (3) the enhancement of financial performance for business sustainability. The findings indicate that the combination of ESG integration and digital transformation is key for BPR to contribute to local economic development. Suggestions for future research include analyzing the impact of ESG implementation and digitalization on BPR's financial performance, as well as customer experiences with digital services.